Developing Virtual Reality (VR) technology in learning Arabic grammar: an insight on needs analysis for Arabic-VR application - Awang Ali, Mohammad Amnan; Md Ghalib, Mohd. Feham (Penerbit Universiti Sains Islam Malaysia, 2024)
The learning of Arabic grammar – which uses textbooks with lengthy details can be transformed into creative and innovative forms through the application of technological advancement. Worldwide educators from diverse backgrounds and cultures are well equipped with the recent teaching methods and tools which are widely used and accessible to guide and nurture the students in a productive and interactive classroom learning environment. Significant studies have indicated that Virtual Reality (VR) is one of the many technological applications for facilitating learning. It is an emerging technology undergoing a rapid transformation in the educational world. However, there is still limited study about the use of VR in Malaysia for teaching and learning a foreign language i.e. Arabic. The usage of this technology has been less explored, particularly from the perspective of students at the university level. Generally, this study employed the Design and Development Research (DDR) approach, and in the first phase of DDR i.e. the needs analysis phase. This phase used a questionnaire on the needs in developing the Arabic-VR Application. Therefore, this study aims to gather students’ perspectives about their needs in developing the Arabic-VR Application using VR technology in learning Arabic grammar. The questionnaire was distributed conveniently to 150 students of various programs at Kolej Universiti Islam Perlis (KUIPs), who took Arabic Language (subject code: DTU2022) as a compulsory subject at the Centre for Languages and General Studies, KUIPs in semester 1, session 2023/2024 of the academic calendar. Quantitative data were then analyzed using the Statistical Package for Social Science (SPSS) application to retrieve frequency distribution, percentages, mean, and standard deviations. The results show a high need to develop the Arabic-VR application for learning Arabic grammar. Findings revealed a positive response to adopting technological tools i.e. VR for language learning as it was positively perceived to increase students’ motivation towards learning Arabic grammar. It is hoped that the findings of this study could benefit the readers and be used as a benchmark for the use of VR in learning Arabic grammar.